METHOD, APPARATUS AND SYSTEM FOR CONTROLLING A WHEEL LODER - WOO-YONG JUNG; CHOON LEE; WOO-SEOK OH; SOO-KYUNG HEO; KWANG-SEOK PARK; YEON-HAENG HEO (2016)
The invention provides a method, an apparatus and a system for controlling a wheel loader. In a method of controlling a wheel loader, signals representing states of work are received from sensors installed in the wheel loader. Signals, which are used for separately judging a plurality of individual loads which are distinguished according to loads required by a series of work performed by the wheel loader, are selected from the received signals. A learnt prediction algorithm is executed for the selected signals and output values representing as to whether or not to be the plurality of individual load states are calculated. The calculated output values are analyzed to determine a current word load state. 本发明提供种轮式装载机的控制方法、控制装置及控制系统。在轮式装载机的控制方法中，从加装于轮式装载机的多个传感器接收表示作业状态的信号。在所接收的信号中，选择分别判断根据所述轮式装载机执行的系列作业所要求的负载而区分的多个个别负载所需的信号。针对所选择的信号，执行已学习的预测算法，算出分别表示是否为所述多个个别负载状态的输出值。分析所述算出的输出值，判断当前的作业负载状态。